FRI0385 UCTD and Progression to SLE. Analysis of a Wide Monocentric Cohort with a Long Follow-Up. (9th June 2015) - Bortoluzzi, A.; Furini, F.; Campanaro, F.; Padovan, M.; Govoni, M.
Abstract : Background: The term undifferentiated connective tissue diseases (UCTD) has been widely used to identify conditions not fulfilling classification criteria for a defined connective tissue diseases (CTD). Recently the introduction of new classification criteria for different CTD allowed to take a significant step forward for their early identification and for a more reliable diagnosis of UCTD. Objectives: To analyze the clinical and serological characteristics of a large cohort of patients (pts) with UCTD and to evaluate: the incidence of Systemic Lupus Erythematosus (SLE) defined according two different "set" of classification criteria for lupus, ACR 1997 and SLICC 2012, in a time frame of 15 years (1999-2013); to analyse clinical and serological data comparing pts affected by stable UCTD to UCTD evolved to SLE. Methods: A cohort of pts referred to our clinic dedicated to UCTD, who met the classification criteria proposed by Mosca et al. [1], were retrospectively analyzed. The pts with a median follow-up less than one year were excluded. Clinical and serological assessment was performed at the time of diagnosis (T0) and at 3 different time points indicated as T1 (time interval between the first and third year), T2 (between the third and fifth year) and T3 (from the fifth to the tenth year). The classification criteria for SLE, ACR 1997 and SLICC 2012, were applied to each patient at time T0, T1, T2 and T3. Results: 329 pts were enrolled. An observation period up to T1 was recorded for the entire sample, up to T2 for 273 pts and 206 pts had completed the follow-up to T3. At T0 no pts met SLE/ACR criteria (according to inclusion criteria of study), whilst 44 pts met SLE/SLICC criteria: 41 females (F, 93.2%) and 3 males (M), mean age 40.1±14 years. Overall, at the end of the observation period, the SLE/SLICC criteria were cumulatively observed in 67 pts (20.4%), while 14 pts met the ACR criteria. In 12 pts both sets of criteria were satisfied. At the end of follow-up, 260 pts did not meet any set of classification criteria (UCTD stable, 79% of the whole population, 253 F and 7 M, mean age 53.6±15.5 years). During the follow-up the rate of progression to SLE was stable over the years, with a number of switch to SLE constant even after 5 years of diagnosis of UCTD. A peak rate of new cases was observed at T3 where five new cases of SLE/ACR (2.4%) and 7 cases of SLE/SLICC (3.4%) were recorded. The baseline clinical and serological characteristics of pts with stable UCTD were compared to pts evolved in SLE. Acute or subacute skin rash (p 0.02), serositis (p 0.03) and the presence of antiphospholipid antibodies (p 0.02) were the variables correlated with the progression to SLE/SLICC. Acute or subacute skin rash (p 0.001) and the presence of antiphospholipid antibodies (p 0.03) were the variables correlated with the evolution to SLE/ACR. Conclusions: From our study in a cohort of UCTD pts the application of the new set of SLICC classification criteria for SLE, compared with the old ACR criteria, would not seem to have contributed significantly in terms of predictability of the evolution towards lupus, but certainly they expanded the number of pts classified as SLE at onset of the disease allowing a certain diagnosis in a greater number of pts who would otherwise be classified as UCTD. References: Mosca M et al. Clin Exp Rheumatol 1999;17:615-620. Disclosure of Interest: None declared